Neuromuscular and postural control in visually and nonvisually impaired judo athletes: case study - Lima Kons, R.; Luiz Sakugawa, R.; Rossato, M.; Diefenthaeler, F.; Detanico, D. (Journal of Exercise Rehabilitation, 2019)
This study aimed to analyze neuromuscular and postural control in visually and nonvisually impaired judo athletes. Two judo athletes, one visually impaired and the other nonvisually impaired, participated in the study. The athletes presented similar demographic, anthropometric, and judo-technical characteristics. They performed maximal isometric handgrip strength (dominant and nondominant hand), vertical jumps (countermovement jump [CMJ] and squat jump [SJ]), and center of pressure assessment in three positions: neutral, anteroposterior, and judo combat base (Migi-shizentai). The main findings showed that the visually impaired athlete presented higher standing balance in the neutral and anteroposterior positions than non-visually impaired athlete (effect size [ES]>2.0). In the Migi-shizentai position, the disparity between both athletes was reduced, particularly in the displacement area (ES=0.52). The visually impaired athlete showed higher performance in the SJ but lesser performance in CMJ and handgrip strength tests than nonimpaired athlete (ES>2.0). We concluded that the postural stability was higher in the visually impaired athlete in the neutral and anteroposterior position, but similar to the nonvisually impaired athlete in Migi-shizentai position, possible due to the influence of judo practice. Moreover, the visually impaired athlete showed higher performance in the SJ than nonvisually impaired.